2007
DOI: 10.1270/jsbbs.57.107
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Quantitative Trait Loci for White-back and Basal-white Kernels under High Temperature Stress in japonica Rice Varieties

Abstract: Several quantitative trait loci (QTLs) associated with the apparent quality of brown rice were identified. QTL analysis was carried out using F 2 and F 3 populations derived from a cross between two japonica varieties, Hana-echizen (high quality of brown rice) and Niigatawase (low quality with numerous white-back and basalwhite kernels). F 2 individuals were grown in paddy fields in 2003, and F 3 lines were grown in paddy fields and in a greenhouse to expose them to high temperature stress during the ripening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 12 publications
0
52
0
2
Order By: Relevance
“…No polymorphic marker on the short arm of chromosome 9 was detected. Kobayashi et al (2007) and Tabata et al (2007) reported similar results for chromosome 9 in temperate japonica crosses, suggesting that chromosome 9 may be highly monomorphic and common by descent in japonica rice.…”
Section: Discussionmentioning
confidence: 64%
“…No polymorphic marker on the short arm of chromosome 9 was detected. Kobayashi et al (2007) and Tabata et al (2007) reported similar results for chromosome 9 in temperate japonica crosses, suggesting that chromosome 9 may be highly monomorphic and common by descent in japonica rice.…”
Section: Discussionmentioning
confidence: 64%
“…Recently, biparental populations of Japanese rice cultivars have been used for genetic analysis of the natural variation in several agronomic traits, such as heading date (Fujino et al 2005, Matsubara et al 2008, culm length (Hori et al 2009), pre-harvest sprouting resistance (Hori et al 2010), eating quality (Kobayashi and Tomita 2008, Takeuchi et al 2008, Wada et al 2008) and grain quality (Kobayashi et al 2007, Tabata et al 2007). These studies have demonstrated that a relatively large allelic difference at a particular locus could be detected despite extremely low sequence diversity in Japanese cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…For simple sequence repeat (SSR) analysis to construct a linkage map, PCR was performed as described in Kobayashi et al (2007).…”
Section: Marker and Statistical Analysesmentioning
confidence: 99%